Peran Risk Aversion sebagai Mediator dalam Hubungan antara Parent Brand Loyalty dan Brand Extension Loyalty - Veronica Jenny Tanzil; Aprihatiningrum Hidayati (Journal of Management and Business Review, 2022)
This paper is aimed to examine the effect of parent brand loyalty to brand extension loyalty, vice versa, also role of parent brand association as moderator and risk aversion as mediator in the relationship of parent brand loyalty and brand extension loyalty. This paper utilizes conclusive research design with predictive causal analytics. Sample collected was from millennial mothers with children ranging from 2-7 years old and are decision makers in purchasing babies and children care products. Primary data were obtained through distributing questionnaires to 100 respondents. The data then processed using MRA for moderating variable analysis and PLS-SEM for mediator variable analysis. This research found that parent brand loyalty has significant direct effect on brand extension loyalty and vice versa, but also partial complementary mediated by risk aversion. While parent brand association proved not to be a moderating role, risk aversion is a partial compensatory mediator in the relationship between parent brand loyalty and brand extension loyalty, hence become the novelty of this study. Future study should consider discussing product categories with special cases, re-examining positive relationship of parent brand association with parent brand loyalty and brand extension loyalty, also examining individual factors that can characterize a millennial cohort consumer.